Turbidity removal by centrifugal microfiltration - Keener, Tim C.; Sewiwat, Narunat; Ratpukdi, Thunyalux (Engineering and Applied Science Research, 2017)
Water turbidity is an important characteristic of surface waters and wastewater treatment plant effluents as well as a key indicator of water quality. Turbidity is the lack of clarity of water caused by microalgae and other particles that attenuates light. The cost of clarifying water can be high. This is primarily due to the physical and chemical steps that must be taken to remove the extremely small entrained particles and colloidal substances that cause high turbidity, and the large amounts of water that generally must be process for such small masses of entrained materials. This paper discusses the results of a series of experiments of a potentially new method of clarifying water by incorporating microfiltration through a high throughput filter operating under a centrifugal force. The results have shown that significant reductions in turbidity can be achieved at relatively high water flux values through a commercially available filter. This indicates the potential of the technology as a water clarifying method by means of this low energy separation device.